Effects of Feed Type on Growth and Food Habits of Green Lobster (Panulirus homarus) Using Smart Lobster Culture - Nurmalasari, Nury; Rita Rostika; Nora Akbarsyah; Irfan Zidni (Universitas Islam Lamongan, 2025)
This study aimed to evaluate the effects of different types of natural feed on the growth performance and feeding habits of green lobsters (Panulirus homarus) using Smart Lobster Culture technology in floating net cages in Pangandaran Regency. The research was conducted over a 60-day cultivation period from February to April 2025. A completely randomized design (CRD) was used with four treatments A: 100% anchovy, B: 80% anchovy, C: 100% rebon, and D: 80% rebon each with four replications. The parameters observed included length and weight growth, survival rate, length percentage per harvest (LPH), efficiency of protein production (EPP), feeding behavior, and water quality. The results showed that the 80% anchovy diet (Treatment B) produced the best outcomes, with an average length increase of 5.08 ± 0.09 cm, a weight gain of 145.13 ± 5.78 g, LPH of 2.09 ± 0.08%, survival rate of ± 98%, EPP of 13.28 ± 0.47%, and a tendency for more active nocturnal feeding behavior with a higher preference for anchovy. Sufficient feed and shelter availability effectively suppressed cannibalism. Water quality parameters remained within optimal ranges: temperature 27.6–29.3 °C, pH 8.1–8.4, salinity 34–36 ppt, and dissolved oxygen (DO) 6.10–8.30 mg/L.